An update on hepatocellular carcinoma in chronic kidney disease - Fabrizi, Fabrizio (2021)
Chronic kidney disease is a major public health issue globally and the risk of cancer (including HCC) is greater in patients on long-term dialysis and kidney transplant compared with the general population. According to an international study on 831,804 patients on long-term dialysis, the standardized incidence ratio for liver cancer was 1.2 (95% CI, 1.0–1.4) and 1.5 (95% CI, 1.3–1.7) in European and USA cohorts, respectively. It appears that important predictors of HCC in dialysis population are hepatotropic viruses (HBV and HCV) and cirrhosis. 1-, 3-, and 5-year survival rates are lower in HCC patients on long-term dialysis than those with HCC and intact kidneys. NAFLD is a metabolic disease with increasing prevalence worldwide and recent evidence shows that it is an important cause of liver-related and extra liver-related diseases (including HCC and CKD, respectively). Some longitudinal studies have shown that patients with chronic hepatitis B are aging and the frequency of comorbidities (such as HCC and CKD) is increasing over time in these patients; it has been suggested to connect these patients to an appropriate care earlier. Antiviral therapy of HBV and HCV plays a pivotal role in the management of HCC in CKD and some combinations of DAAs (elbasvir/grazoprevir, glecaprevir/pibrentasvir, sofosbuvir-based regimens) are now available for HCV positive patients and advanced chronic kidney disease. The interventional management of HCC includes liver resection. Some ablative techniques have been suggested for HCC in CKD patients who are not appropriate candidates to surgery. Transcatheter arterial chemoembolization has been proposed for HCC in patients who are not candidates to liver surgery due to comorbidities. The gold standard for early-stage HCC in patients with chronic liver disease and/or cirrhosis is still liver transplant.